Limitations of the right to personal data protection and the right to secrecy of correspondence under martial law in Ukraine - Ihor ANDRONOV; Larysa DIDENKO; Semen REZNICHENKO; Roman POZHODZHUK; ROMANIUK, Vitaliia (Revista Jurídica Portucalense, 2024)
The right to personal data protection and secrecy of correspondence are important components of the right to privacy, one of the fundamental human rights. In modern society, private life becomes especially vulnerable, taking into account the possibilities of modern technologies. The intervention into the private life can be almost unlimited unless there are some legislative rules which prevent such intervention. Therefore, it is very important to develop reliable mechanisms for the protection of the right to privacy and its elements, in particular, the right to personal data protection and the right to secrecy of correspondence. Unfortunately, the state of ensuring these rights in Ukraine is imperfect. The legislation aimed at protecting personal data does not meet European standards. This state of affairs is especially disturbing in terms of martial law imposed in Ukraine, when it is allowed to limit constitutional human rights, in particular, the right to privacy. It is important to determine the permissible limits of such restrictions, and to provide reliable mechanisms for the protection of these rights in case of exceeding the permissible interference in private life under martial law.